La enseñanza de conceptos básicos de química orgánica y las herramientas Web 2.0 en grupos masivos a nivel universitario - Romero, Rosaura M. (2019)
A large group together with the fact that organic chemistry is commonly regarded as difficult creates challenges for the instructor. In this paper we describe the evaluation of the effectiveness of implementing Web 2.0 tools in organic chemistry lecture on students' understanding of basic concepts in comparison with the absence of such tools in large groups. The study used a mixed method design that encompassed 537 students in six separate sections of two courses, four accelerated and two general organic chemistry courses. All the sections but three experienced the standard lecture environment without intervention. The intervention consisted of a blog designed specifically for this research, which used entries regarding key concepts with selected videos. Instructors and students were invited to respond to various instruments for research data gathering. Those instruments included questions concerning previous knowledge of chemistry, covered information to acknowledge the use of Web 2.0 by instructors and students, and involved items to discover whether the tools were perceived useful for the students. The study used only data from the students who attended class on a regular basis and completed the test and the questionnaires. The impact of the use of Web 2.0 on student achievement was obtained from the students' grades on the first examination of the term. The participants' perception was that the tools are useful for the teaching-learning process and the blog and videos had a positive impact on their academic performance